Role Of Meteorological-Gaseous Factors In Distribution Of Coarse-Particles (PM10) In Penang. - Satheraman, Kashuri Redi (2016)
This study aims to determine the inﬂuence of meteorological-gaseous factors in the distribution of Particulate Matter-10 (PM1O) at Penang. Meteorological parameters such as temperature, rainfall, humidity, wind speed and mean sea level (MSL) pressure was obtained from Meteorological Department of Malaysia for the month May 2014 to September 2014. Concentration values of PM10, sulphur dioxide (S02), nitrogen dioxide (N02), ozone (O3) and carbon monoxide (CO) from three different sites namely; industrial area, roadside and residential site was obtained from Malaysian Department of Environment (DOE) for the month May 2014 to September 2014. Descriptive analysis of air pollutants and API values was constructed along with box plot analysis of PM10 concentration distribution and graph analysis between API values with PM10 concentration. Graphs of PM10 concentration relationship with meteorological parameters were plotted together. Pearson correlation analysis was used to determine the relationship between the gaseous pollutants as well to detennine the relationship between PM10 concentration and meteorological factors. Strong correlation was obtained among PM10-CO and PM10—O3. Correlation between meteorological parameters and PM10 concentration showed that temperature has positive correlation at industrial area, roadside and residential area. MSL pressure also showed two weak positive signiﬁcant correlations and one negative correlation showing that at the sampling areas temperature and MSL pressure have signiﬁcant relationship. The result from this study could provide some useful information on the inﬂuence of meteorological-gaseous inﬂuences on PM10 distributions and ways to mitigate air pollution.